Unani medicine in the making practices and representations in 21st century India - Stiedenroth, Kira Schmidt (Amsterdam University Press, 2020)
In Unani Medicine in the Making, Kira Schmidt Stiedenroth examines the contemporary institutions and practices of Graeco-Islamic healing in India. Drawing on interviews with practitioners, clinical observations, and Urdu sources, the book focuses on Unani's multiplicity, scrutinizing apparent tensions between the understanding of Unani as a system of medicine and its multiple enactments as Islamic medicine, medical science, or alternative medicine. Ethnographic details provide vivid descriptions of the current practices of Unani in India and invite readers to rethink the idea that humoral medicine is incommensurable with modern science. Ultimately, the book also discusses the relationship of Unani with Muslim communities, examining the growing practice of Prophetic Medicine in Urban India and the increasing representation of Unani as Islamic Medicine.